2022
DOI: 10.3390/f13010079
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Soil Extracts from Selangor Peat Swamp and Pristine Forest Soils on the Growth of Green Microalgae sp.

Abstract: Microalgae are widely utilized in commercial industries. The addition of a modified artificial medium (soil extract) could enhance their growth. Soil extract collected from the Raja Musa peat swamp and mineral soil from the Ayer Hitam Forest Reserve (AHFR), Selangor, Malaysia, were treated using various extraction methods. Carteria radiosa PHG2-A01, Neochloris conjuncta, and Nephrochlamys subsolitaria were grown in microplates at 25 °C, light intensity 33.75 µmol photons m−2s−1 for 9 days. N. conjuncta dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The reserve's topography features undulating terrain interspersed with water bodies and intricate drainage patterns typical of peatland ecosystems. In terms of climate, the RMFR experiences a tropical rainforest climate with relatively high humidity and abundant rainfall throughout the year [18]. These climatic conditions, coupled with the presence of peat soils, contribute to the elevated risk of forest fires within the reserve.…”
Section: Data Preparationmentioning
confidence: 99%
“…The reserve's topography features undulating terrain interspersed with water bodies and intricate drainage patterns typical of peatland ecosystems. In terms of climate, the RMFR experiences a tropical rainforest climate with relatively high humidity and abundant rainfall throughout the year [18]. These climatic conditions, coupled with the presence of peat soils, contribute to the elevated risk of forest fires within the reserve.…”
Section: Data Preparationmentioning
confidence: 99%
“…Research on microalgae has revealed that heavy metals can enter plant cells either through active transportation or endocytosis facilitated by plant chelating proteins, thereby mitigating the toxicity of heavy metals. However, when an excess of heavy metals accumulates, heavy metal ions bind to thiol groups within protein cysteine, disrupting the protein structure or displacing essential elements [64]. The emergence of new shoots indicates healthy growth and robust stress resistance in plants.…”
Section: New Shoot Growthmentioning
confidence: 99%
“…Also to soil improvement, extra fertilizer containing N, P and K elements is also good and important to give to plants to increase nutrient availability so that optimal biomass production implies increasing carrying capacity [52]. Very acidic soils are followed by very low to low macronutrient deficiencies [53][54][55].…”
Section: Plant Type Minimum Phmentioning
confidence: 99%